Formulation and Evaluation of Pulp Devitalization Paste Combination of Jatropha Curcas L. and Piper Crocatum Leaves Extract - Damarwati, Vella Lailli; Wahid, Rahmat A Hi; Primasari, Dyani; Harimurti, Sabtanti; Labibah, Lana; Syahrani, Syahrani; Krisridwany, Annisa (Universitas Ahmad Dahlan, 2022)
Dental caries require operative techniques such as pulp devitalization, but pulp devitalization materials that are often used by dentists have serious adverse effects that need to be considered, such as gingival injury and alveolar bone necrosis. Hence, the aim of the present study was to develop natural ingredients as an alternative to pulp devitalization from a combination of Jatropha curcas (Jatropha curcas L.) and red betel leaf extract (Piper crocatum) in the form of a paste and then conducting physical evaluation tests, Cyclooxygenase-2 (COX-2) tests, and also histopathological picture tests to the sample. The formulation of the pasta sample was carried out by the trituration method. Formulation I (FI) contained 25% of Jatropha resin, 0.25% red betel leaf extract, and 25% Jatropha resin, 0.5% red betel leaf extract for Formulation II (FII). The paste produced was then evaluated for physical properties which consisted of organoleptic, homogeneity, pH, spreadability, adhesion, and anti-inflammatory power using test animals with COX-2 expression number parameters. The FI and FII treatment groups had met the requirements as paste formula. In the COX-2 expression test, FI has a COX-2 expression percentage value of 0.38% and a COX-2 suppression percentage value of 0.62%, while FII has a COX-2 expression percentage value of 0.59% and a COX-2 expression percentage of 0.59% and suppression of COX-2 of 0.41%. The optimal concentration of the paste formulation is the paste with a combination of 25% jatropha latex and 0.25% red betel leaf extract had been shown to have potential as an alternative to pulp devitalization